Tetraspanin CD63 controls basolateral sorting of organic cation transporter 2 in renal proximal tubules. Issue 4 (28th December 2016) - Schulze, Ulf; Brast, Sabine; Grabner, Alexander; Albiker, Christian; Snieder, Beatrice; Holle, Svenja; Schlatter, Eberhard; Schröter, Rita; Pavenstädt, Hermann; Herrmann, Edwin; Lambert, Carsten; Spoden, Gilles A.; et al.
Abstract : CD63 is a ubiquitously expressed member of the tetraspanin superfamily. Using a mating‐based split‐ubiquitin–yeast 2‐hybrid system, pull‐down experiments, total internal reflection fluorescence microscopy, Förster resonance energy transfer, and biotinylation assays, we found that CD63 interacts with human organic cation transporter 2 (hOCT2), which transports endogenous and exogenous substrates, such as neurotransmitters and drugs in several epithelial cells. CD63 overexpression affects cellular localization of hOCT2 expressed in human embryonic kidney (HEK)293 cells. Studies with CD63‐knockout mice indicate that in renal proximal tubules, CD63 determines the insertion of the mouse ortholog of the transporter into the proper membrane domain and mediates transporter regulation by trafficking processes. In polarized Madin‐Darby kidney canine kidney (MDCK) epithelial cells, CD63 and hOCT2 colocalize with the small GTPase Rab4, which controls the rapid recycling from sorting endosomes back to the cell surface. Suitable negative and positive control experiments were performed for each experimental approach. Empty vector transfected cells and wild‐type mice were used as control. CD63 seems to play a role in the recycling of hOCT2 from endosomes to the basolateral membrane in polarized epithelia. These data indicate that CD63 has a previously uncharacterized function in regulating trafficking of specific membrane proteins in polarized cells. —Schulze, U., Brast, S., Grabner, A., Albiker, C., Snieder, B., Holle, S., Schlatter, E., Schröter, R., Pavenstädt, H., Herrmann, E., Lambert, C., Spoden, G. A., Florin, L., Saftig, P., Ciarimboli, G. Tetraspanin CD63 controls basolateral sorting of organic cation transporter 2 in renal proximal tubules. FASEB J . 31, 1421–1433 (2017) www.fasebj.org